Islamic theology and philosophy : studies in honor of George F. Hourani - Hourani, George Fadlo; Marmura, Michael E., 1929- (Albany : State University of New York Press, 1984)
English and French. Includes bibliographical references and index.
The metaphysics of efficient causality in Avicenna (Ibn Sina) / Michael E. Marmura -- Remarks on Averroes' decisive treatise / Muhsin Mahdi -- Eternity and origination : Averroes' discourse on the manner of the world's existence / Barry S. Kogan -- ʻAbd al-Latif al-Baghadi's Epitome of the Kalam fi Mahd al-Khayr (Liber de Causis) / Richard C. Taylor -- Afdal al-Din Kashani and the philosophical world of Khwaja Nasir al-Din Tusi / Seyyed Hossein Nasr -- Theism, mysticism and scientific history in Ibn Khaldun / Fablou Shehadi.
English and French.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hourani, George Fadlo; Hourani, George Fadlo; Hourani, George Fadlo; Islamic philosophy; Islam -- Doctrines; Islam -- Doctrines; Philosophie islamique; BIOGRAPHY & AUTOBIOGRAPHY -- General; PHILOSOPHY -- Eastern; Islam -- Doctrines; Islamic philosophy; Islamische Theologie; Aufsatzsammlung; Islamische Philosophie; Bibliografie; Islamitische filosofie; Islam; Essays